Microbeam radiation therapy: Clinical perspectives. Issue 6 (September 2015) - Grotzer, M.A.; Schültke, E.; Bräuer-Krisch, E.; Laissue, J.A.
Abstract Microbeam radiation therapy (MRT), a novel form of spatially fractionated radiotherapy (RT), uses arrays of synchrotron-generated X-ray microbeams (MB). MRT has been identified as a promising treatment concept that might be applied to patients with malignant central nervous system (CNS) tumours for whom, at the current stage of development, no satisfactory therapy is available yet. Preclinical experimental studies have shown that the CNS of healthy rodents and piglets can tolerate much higher radiation doses delivered by spatially separated MBs than those delivered by a single, uninterrupted, macroscopically wide beam. High-dose, high-precision radiotherapies such as MRT with reduced probabilities of normal tissue complications offer prospects of improved therapeutic ratios, as extensively demonstrated by results of experiments published by many international groups in the last two decades. The significance of developing MRT as a new RT approach cannot be understated. Up to 50% of cancer patients receive conventional RT, and any new treatment that provides better tumour control whilst preserving healthy tissue is likely to significantly improve patient outcomes.